Timing of Colonization of Caries-Producing Bacteria: An Approach Based on Studying Monozygotic Twin Pairs - Michelle R. Bockmann; Abbe V. Harris; Corinna N. Bennett; Ruba Odeh; Toby E. Hughes; Grant C. Townsend (Hindawi Limited, 2011)
Findings are presented from a prospective cohort study of timing of primary tooth emergence and timing of oral colonization of Streptococcus mutans (S. mutans) in Australian twins. The paper focuses on differences in colonization timing in genetically identical monozygotic (MZ) twins. Timing of tooth emergence was based on parental report. Colonization timing of S. mutans were established by plating samples of plaque and saliva on selective media at 3 monthly intervals and assessing colony morphology. In 25% of individuals colonization occurred prior to emergence of the first tooth. A significant proportion of MZ pairs (21%) was discordant for colonization occurring before or after first tooth emergence, suggesting a role of environmental or epigenetic factors in timing of tooth emergence, colonization by S. mutans, or both. These findings and further application of the MZ co-twin model should assist in development of strategies to prevent or delay infection with S. mutans in children.